The Carolingian Church and the Book - McKitterick, Rosamond (Studies in church history, 2004)
In 849, Gottschalk of Orbais was summoned to the Synod of Quierzy. From his own studies of the patristic theologians he had formed views on predestination that had found little favour with the established Church of his day. No text of the proceedings at Quierzy survives but we do have reports from eye-witnesses in the contemporary Annals of St Bertin - interpolated by Archbishop Hincmar of Rheims to Gottschalk’s disadvantage - and by Florus the Deacon of Lyons. Hincmar is very scathing on how much Gottschalk’s learning had led him astray; he was too erudite for his own good. Hincmar tells us that at the synod, Gottschalk was accused of errant views, condemned, flogged, and compelled to burn the books containing his teachings (librosque suarum adsertionum). Florus the Deacon, however, provides crucial extra information. While Hincmar gives the impression that Gottschalk went to Quierzy more or less to be publicly punished, Florus’ account suggests that Gottschalk, at least as far as he, Gottschalk, was concerned, went to engage in dispute. He may even have been buoyed up with the hope of convincing his audience of bishops and abbots from the ecclesiastical province of Rheims, including Paschasius Radbertus of Corbie and Gottschalk’s own abbot from Orbais (in the diocese of Soissons), that he was justified in his views. Florus tells us that what Gottschalk had to burn were the sections from the Bible and patristic writings that vindicated his opinions and that he had brought with him to the synod. Gottschalk’s reference collection sounds very much like the dossiers assembled at other councils (not least Nicaea II in 787) compiled from authoritative writings to support views maintained in discussion.